Pelatihan Pembuatan Minuman Herbal Maiq Tulen sebagai Inovasi Produk Kelompok Tani ‘Pade Angen’ di Desa Peresak Kabupaten Lombok Barat - Rosalina Edy Swandayani; Meilinda Pahriana Sulastri; Mimi Cahayani (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This service activity aims to improve the understanding and skills of farmer groups in innovating Maiq Tulen herbal drinks. This method of implementing service using training with partners was a member of the Pade Angen Farmer Group in Peresak Village, West Lombok. Evaluation of activities was carried out by providing pre test and post test to participants to measure the success of service activities, which were then analyzed descriptively. The results of this service activity showed that the increasing understanding and skills of Pade Angen farmer group members in making Maiq Tulen herbal drinks into powder drinks based on their uses, namely Pegal Linu, Stamina, and Femininity to produce Maiq Tulen products that were more varied and favored by consumers. In addition, farmer groups also could package products. Based on the activities' results, the PkM team also assisted in the form of flour equipment, stoves, packaging, and several other supporting tools.Â